After the war
1 online resource (xxxii, 385 pages)
Keywords: "After the War presents a panoramic view of social, political, and economic change in post-Civil War America by examining its journalism, from coverage of politics and Reconstruction to sensational reporting and images of the American people. The changes in America during this time were so dramatic that they transformed the social structure of the country and the nature of journalism. By the 1870s and 1880s, new kinds of daily newspapers had developed. New Journalism eventually gave rise to Yellow Journalism, resulting in big-city newspapers that were increasingly sensationalistic, entertaining, and designed to attract everyone. The images of the nation's people as seen through journalistic eyes, from coverage of immigrants to stories about African American "Black fiends" and Native American "savages," tell a vibrant story that will engage scholars and students of history, journalism, and media studies.?"--Provided by publisher.